2020
DOI: 10.1177/1748006x20901981
|View full text |Cite
|
Sign up to set email alerts
|

Advanced time-dependent reliability analysis based on adaptive sampling region with Kriging model

Abstract: Aiming at accurately and efficiently estimating the time-dependent failure probability, a novel time-dependent reliability analysis method based on active learning Kriging model is proposed. Although active surrogate model methods have been used to estimate the time-dependent failure probability, efficiently estimating the time-dependent failure probability by a fewer computational time remains an issue because screening all the candidate samples iteratively by the active surrogate model is time-consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The proposed method is directly compared with crude MCS. The example is widely used in the literature as a benchmark example [23,30,39,52]. As shown by Fig.3, it deals with a steel bending and corroded beam.…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method is directly compared with crude MCS. The example is widely used in the literature as a benchmark example [23,30,39,52]. As shown by Fig.3, it deals with a steel bending and corroded beam.…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
“…To handle problems involving time-consuming codes, the idea of surrogate model-based methods for time-independent reliability analysis is usually adopted. Kriging [29][30][31] and polynomial chaos expansion [32][33][34] are used to reduce the number of evaluations of timeconsuming models. Their basic idea is to construct surrogate models using a limit number of design points, and then replace the original time-consuming model in time-variant reliability procedures.…”
Section: Introductionmentioning
confidence: 99%
“…6,26,27 Specifically, Zhou et al 28 developed a Kriging-based method to reduce the computational cost of the uncertainty analysis of motion errors by defining two motion errors. Shi et al 29 developed a novel time-dependent reliability analysis method based on active Kriging to estimate the time-dependent failure probability accurately and efficiently. Yang et al 30,31 reported two novel methods combined the active kriging model with IS to solve problems with very small failure probability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often combined with other methods to evaluate time-variant probability of failure, such as surrogate-model-based methods and a part of first-crossing-based methods. A great amount of the literature in regards to crude MCS as the benchmark compares efficiency and accuracy of other methods [6,24,25,30]. Subset simulations (SS), such as Markov Chain Monte Carlo (MCMC), SS with splitting method [31,32] and SS with splitting and partitioning in time [33], are efficient methods for precisely evaluating time-variant probability of failure.…”
Section: Introductionmentioning
confidence: 99%